Low-gravity L Dwarfs Are Likely More Variable. Issue Volume 10:Issue S314(2015) (November 2015) - Metchev, Stanimir; Heinze, Aren; Apai, Daniel; Flateau, Davin; Radigan, Jacqueline; Burgasser, Adam; Marley, Mark; Artigau, Étienne; Plavchan, Peter; Goldman, Bertrand
Abstract: In the "Weather on Other Worlds" Spitzer Exploration Science program, we surveyed 44 nearby L3–T8 dwarfs for spot-induced rotational variability. Among single L3–L9.5 dwarfs, we found that 80% are variable at >0.2% in the 3–5 μm wavelength range, while 36% of T0–T8 were variable at >0.4%. Taking into account viewing angle and sensitivity considerations, both of these findings are consistent with spots being present on ~100% of L3–T8 dwarfs. Intriguingly, we find a tentative association (92% confidence) between low surface gravity and high-amplitude variability among L3–L5.5 dwarfs. Although we can not confirm whether lower gravity is also correlated with a higher incidence of variables, the result is promising for the characterization of directly imaged young extrasolar planets through variability.